MEMBANGUN KEMAMPUAN MEMBACA AL-QUR’AN MAHASANTRI MELALUI PEMBELAJARAN AL-QUR’AN DI YPPP. AN-NURIYAH SURABAYA - Kurnia, Alaika M Bagus; Ghofur, Mochamad Abdul (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
Surabaya, is a concrete location to be the object of discussion about how the Qur'anic scientific development in it. Because, the public activity is quite high, causing the Qur'an to only be discussed at the level of the clergy or santri. Another concrete proof, in the era of the 90s, was the Al-Qur'an Education Park (TPQ) which had been mushrooming in village corners for a long time, now it is difficult to maintain both management and resources. So that at this time in the 2000s TPQ was said to be very backward because Islamic schools and others both at the elementary and secondary levels had offered tartil learning programs reading Al-Qur'an. In fact, there are also schools that incorporate Qur'anic learning on regular curricula or subjects.Methodologically, this research is qualitative research using the Participatory Action Research approach. This approach is intended to see, hear, and at the same time understand the social symptoms that exist in mahasantri and the surrounding community.From the author's observation directly, it can be seen that the ability of students in YPPP an-Nuriyah does vary. In general, they can be said to be in the medium level and above. With the similarity of sexes, that is, all students in this pesantren are women, the Qur'anic learning for them is easier and more supportive for their reading.